2016
DOI: 10.3168/jds.2016-10914
|View full text |Cite
|
Sign up to set email alerts
|

A process efficiency assessment of serum protein removal from milk using ceramic graded permeability microfiltration membrane

Abstract: Microfiltration (MF) is a well-known process that can be used in the dairy industry to separate caseins from serum proteins (SP) in skim milk using membranes with a pore diameter of 0.1μm. Graded permeability ceramic membranes have been studied widely as means of improving milk fractionation by overcoming problems encountered with other MF membranes. The ideal operating parameters for process efficiency in terms of membrane selectivity, permeate flux, casein loss, SP transmission, energy consumption, and dilut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 25 publications
2
22
1
Order By: Relevance
“…Although several studies have characterized the separation performance of MF membranes, very few evaluated process efficiency and quantification of energy consumption in MF. The study done by Tremblay-Marchand et al (2016) showed that when the CF was increased to 3.0× for a 0.1-µm GP membrane, energy consumption and total CN loss increased, whereas the SP removal rate decreased. Diafiltration allowed an increase in total SP removal but resulted in a substantial increase in energy consumption and CN losses (Tremblay-Marchand et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have characterized the separation performance of MF membranes, very few evaluated process efficiency and quantification of energy consumption in MF. The study done by Tremblay-Marchand et al (2016) showed that when the CF was increased to 3.0× for a 0.1-µm GP membrane, energy consumption and total CN loss increased, whereas the SP removal rate decreased. Diafiltration allowed an increase in total SP removal but resulted in a substantial increase in energy consumption and CN losses (Tremblay-Marchand et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…One of the important and widespread applications of microfiltration membranes is bacteria removal in different industries such as water treatment, food industry, and medicine . In this study, the bacteria removal performance of the prepared PES/PVP/TEG microfiltration membranes was investigated by filtration of bacteria suspension with initial concentration of 10 6 –10 7 CFU/mL and growth of the filtrated solution on the agar palate.…”
Section: Resultsmentioning
confidence: 99%
“…Again, the permeability was used to compare the two membrane types. The true protein (TP) rejection coefficient was also calculated [17].…”
Section: Methodsmentioning
confidence: 99%
“…Skim milk, retentate, permeate, and whey samples were analyzed according to the methodology described by Tremblay-Marchand et al [17]. Briefly, the contents of the TP, CN, and non-protein nitrogen (NPN) were determined by the Kjeldahl digestion (AOAC International 991.20, 998.05, and 991.21, respectively).…”
Section: Methodsmentioning
confidence: 99%